التنمية المُستدامة في العراق: التحديات والمعالجات (قضايا سياسية, 2022)
The sustainable development with its economical، sociable ،environmental sectors formed an essential rule provide the needs of the country ،and this is possible to be accomplished through realizing the challenges we faced ، so the renewed development aimed to find a balance between the economic needs without exhaustion the natural sources ،in consideration the environmental factors ،whereas the aim of this development is human himself ، so the renewed development is in need of keeping and saving the capability of futural generations of from the benefit of natural sources and concentrated this study on the concept of sustainable development and its economical ،social ،environmental factors ،besides the wise judgment ،and this study discussed the aims of the sustainable development and updated it by conclusions and recommendations about the necessity of the activated the programs of sustainable development to make it progressed to keep at the least of respectable living and healthy life and education for every individual in just، fair form for all without any discriminations.